2013
DOI: 10.1111/mmi.12396
|View full text |Cite
|
Sign up to set email alerts
|

Dual input control: activation of the Bartonella henselaeVirB/D4 type IV secretion system by the stringent sigma factor RpoH1 and the BatR/BatS two‐component system

Abstract: SummaryThe co-ordinated expression of virulence factors is a critical process for any bacterial pathogen to colonize its host. Here we investigated the mechanisms of niche adaptation of the zoonotic pathogen Bartonella henselae by combining genetic approaches and shotgun proteomics. We demonstrated that expression of the VirB/D4 type IV secretion system (T4SS) and its secreted effector proteins require the alternative sigma factor RpoH1, which levels are controlled by the stringent response (SR) components Dks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 85 publications
(225 reference statements)
2
38
0
Order By: Relevance
“…To characterize BaGTA behavior across time in a population of Bartonella cells, we constructed a reporter strain carrying a transcriptional gfp fusion to the phage-related tail collar gene (BH13960, renamed bgtC ) located at the BaGTA locus. We monitored single-cell BaGTA expression dynamics upon growth in medium M199/10% fetal calf serum (hereafter M199), a host cell-free system commonly used to study the temporal progression of the Bartonella virulence program (Québatte et al., 2013). Time-course analysis using flow cytometry (fluorescence-activated cell sorting [FACS]) revealed that the gfp-bgtC reporter was heterogeneously expressed within a subpopulation of cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To characterize BaGTA behavior across time in a population of Bartonella cells, we constructed a reporter strain carrying a transcriptional gfp fusion to the phage-related tail collar gene (BH13960, renamed bgtC ) located at the BaGTA locus. We monitored single-cell BaGTA expression dynamics upon growth in medium M199/10% fetal calf serum (hereafter M199), a host cell-free system commonly used to study the temporal progression of the Bartonella virulence program (Québatte et al., 2013). Time-course analysis using flow cytometry (fluorescence-activated cell sorting [FACS]) revealed that the gfp-bgtC reporter was heterogeneously expressed within a subpopulation of cells.…”
Section: Resultsmentioning
confidence: 99%
“…The spoT gene encodes for an Rhs guanosine-tetraphosphate synthase enzyme (ppGpp synthase). SpoT consists of an N-terminal synthetase domain that catalyzes the formation of the stringent response alarmone ppGpp (Québatte et al., 2013). The alarmone ppGpp functions by binding to target proteins, leading to bacterial cells shutting down active growth and entering a dormant state that promotes survival (Steinchen and Bange, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations